Cross-layer energy efficient protocol for QoS provisioning in wireless sensor network. (2017) - Bourmada, Amal; Bilami, Azeddine
Ensuring (QoS) in wireless sensor networks (WSNs) is a challenging issue due to the lack of resources and energy exhausting of sensor nodes. In this paper we propose a new QoS aware routing protocol for multi-hop wireless sensor networks based on cross-layer interaction between the network, MAC and physical layers. At physical layer, a link quality estimator is studied for the purpose of evaluating link quality. At MAC layer, a differentiated services mechanism is used to distinguish between real time and non-real time packets and to allocate more channel resources for real time traffic; TDMA slots also have been modified to allocate more and earlier slots to real time packets. At network layer, a routing path selection algorithm is introduced for QoS optimisation. Simulation results show that our proposed protocol improves network's performances in terms of energy efficiency and QoS.